Influence Of Servant Leadership, Compensation And Motivation To Organizational Citizenship Behavior On Blooms Coffee & Eatery Surakarta - Ansharifqi, Irsyad; Damaningrum, Kurniawati; Wijiastuti, Sri (Agribusiness Department, Agriculture Faculty, Tunas Pembangunan University, Surakarta, Indonesia, 2025)
The objectives of this research are 1) To test and measure the influence of servant leadership on organizational citizenship behavior. (2) to test and measure the effect of compensation on organizational citizenship behavior. (3) to test and measure the influence of motivation on organizational citizenship behavior. This research was conducted on employees of Blooms Coffee & Eatery Surakarta. The population in this research is all employees at Blooms Coffee & Eatery which consists of 3 divisions, namely Server/Waiters, Barista and Kitchen, namely 22 employees. This research was conducted using a saturated sampling method because the employee population was relatively small, namely 22 people. The data analysis method used is multiple linear regression analysis. Based on the results of the analysis, it is known that: (1) Servant leadership has a positive and significant effect on Organizational Citizenship Behavior, (2) Compensation has an effect but is not significant on Organizational Citizenship Behavior, (3). Motivation has a positive and significant effect on Organization Citizenship Behavior.